Spectrofluorometric assay for rapid detection of total and fecal coliforms from surface water. - Park, S J (1995)
With a spectrofluorometer, the length of the incubation time required in the fluorogenic assay was reduced to 12 h. The threshold emissions for reading the fluorogenic reaction by the spectrofluorometer were 5 and 10 U for lauryl tryptose broth media containing 4-methylumbelliferyl-beta-D-galactoside and 4-methylumbelliferyl-beta-D-glucuronide, respectively. These two kinds of threshold units were equivalent to known concentrations of free 4-methylumbelliferone of 2.5 and 6 microM, respectively, in lauryl tryptose broth media.